Semiotic Analysis of Bullying Representation in Korean Drama "The Glory" - Yudistira, Alfan; Meifilina, Andiwi; Siswati, Endah (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2024)
Korean dramas often tell about issues that often occur in society, one of which is bullying. One of the Korean dramas that represents the phenomenon of bullying is "The Glory". This research aims to find out how bullying is represented in the Korean drama "The Glory" by analyzing scenes that display forms of bullying using Roland Barthes' semiotic analysis.The results of this research found 12 scenes in 7 episodes that represent bullying behavior in the Korean drama "The Glory". The representation of bullying in the Korean drama "The Glory" shows various forms of bullying such as direct physical contact, direct verbal contact, direct non-verbal behavior, cyberbullying, and sexual harassment. The perpetrators of bullying feel they are powerful and have the power to act as they please, especially to students who appear weak and have no power. They come from rich or influential families and abuse their victims with impunity from the authorities. The perpetrators also have no sense of guilt at all, and even consider the bullying they do as entertainment.